Using achievements of fruit crop genetics and breeding: a contribution from the Michurinsk Department of the Vavilov Society of Geneticists and Breeders - N. I. Savel’ev; N. N. Savel’eva (Вавиловский журнал генетики и селекции)
The Michurinsk Department of the Vavilov Society of Geneticists and Breeding Scientists (VOGiS) was formed in 1966 after the constituent congress of VOGiS and nowadays includes 54 members. The scientists are engaged in 4 scientific institutions affiliated with FASO of Russia. The paper presents investigations of the individual genetics of leading fruit crops (pear, cherry, apple), identified genes, regularities of inheriting resistance to low temperatures, the most harmful diseases and several characters responsible for fruit quality. Some genes were identified for the first time. These are genes regulating Coccomyces hiemalis Higg. resistance (A), retarded growth habit in cherry (O2), astringency (Ta) and juiciness (Su) of fruit in pear. On the base of hybridological analysis and DNA marking, genotypes were identified. These genotypes carry target alleles of the following genes: columnar growth habit (Co) in apple, dwarf trait (PcDw) in pear, retardant growth (O2) in cherry. It was found that the markers C18470-25831, Mdo.chr 10.12, Co04R12 do not always show robust results for screening of young apple seedlings with columnar growth habit (Co) because they are identified as non-columnar forms. The primer pairs of 29f1 и jwi1r are the most robust ones for identification of columnar genotypes. These primers amplify specific PCR product of 586 bp (5’CR). On the basis of molecular-genetic analysis of apple initial forms and hybrid seedlings, there were identified targeted alleles of monogenic scab resistance genes including dominant homozygous genotype (Rvi6Rvi6) and also alleles of genes involved in the control of the biosynthesis of ethylene (Md-ACS1 and Md-ACO1) and expansin (Md-Exp7) controlling fruit long shelf life and pulp firmness.